The Brighton Collaboration standardized template for collection of key information for benefit-risk assessment of inactivated viral vaccines. Issue 39 (3rd September 2020) - Kochhar, Sonali; Excler, Jean-Louis; Kim, Denny; Robertson, James S.; Fast, Patricia E.; Condit, Richard C.; Drew, Stephen; Wood, David; Gurwith, Marc; Klug, Bettina; Whelan, Mike; Khuri-Bulos, Najwa; et al.
Abstract: Inactivated viral vaccines have long been used in humans for diseases of global health threat and are now among the vaccines for COVID-19 under development. The Brighton Collaboration Viral Vector Vaccines Safety Working Group (V3SWG) has prepared a standardized template to describe the key considerations for the benefit-risk assessment of inactivated viral vaccines. This will help key stakeholders to assess potential safety issues and understand the benefit-risk of the vaccine platform. The standardized and structured assessment provided by the template would also help to contribute to improved communication and support public acceptance of licensed inactivated viral vaccines.